Jun Cruz Reyes won the National Book Award for best book in fiction - Reyes, Jun Cruz (Animo Repository, 1982)
Jun Cruz Reyes of the Philippine Studies Department won the National Book Award for Best Book in Fiction from the Manila Critics Circle for his book, Utos ng Hari at Iba Pang Kuwento. As winner, he was awarded the Abueva trophy. He was also included in the World Literature listing, making Utos the first book by a Filipino to appear in the listing.